Pembelajaran Partisipasi Aktif Siswa Tunagrahita Di TK Talenta Semarang Ditinjau Dari Aspek Pedagogis Dan Ekologis - Robaiyani, Siti; Ahyauddin, M. Mawahib; Rahmania, Afifah; Masfia, Irma; Fahmy, Zulfa (unprimdn.ac.id, 2024)
A critical element in the learning process is student participation. However, children with disabilities sometimes have obstacles to participate in the classroom. Therefore, this study focuses on observing the active participation of students with disabilities in Talenta Semarang Kindergarten and the methods used to stimulate participation. Active participation is examined from two aspects, namely ecology and pedagogy. This research is qualitative, using observation and interview data collection methods. The analysis technique used is descriptive phenomenology, which is a technique for understanding the subject's experience by describing the essential features of a phenomenon without interpreting it. The study results showed that the students with disabilities at Talenta Semarang Kindergarten could show limited participation levels in the ecological and pedagogical aspects. In this case, each student showed different levels according to their abilities. In addition, teachers can also show some methods to provoke students with disabilities to participate in the learning process in the classroom. This research also discusses the obstacles and challenges faced by students with disabilities in the learning process.